THE ROLE OF INFORMATION TECHNOLOGIES IN THE MODERN ECONOMY - Kenjayeva Sabohat Safarovna (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The article analyzes the role of information technologies in the current state of the economy. At first, the opinions of experts from other fields who do not work in the field are presented about the role of information technologies or other types of technologies in the modern economy. Then, information, at the same time, how exactly information technology has gained an important place in the economy will be discussed. Finally, information technologies that perform important tasks in the economy and are widely used will be touched upon.